2014
DOI: 10.11646/phytotaxa.9.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Fungal symbioses in bryophytes: New insights in the Twenty First Century

Abstract: Fungal symbioses are one of the key attributes of land plants. The twenty first century has witnessed the increasing use of molecular data complemented by cytological studies in understanding the nature of bryophyte-fungal associations and unravelling the early evolution of fungal symbioses at the foot of the land plant tree. Isolation and resynthesis experiments have shed considerable light on host ranges and very recently have produced an incisive insight into functional relationships. Fungi with distinctive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
126
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(131 citation statements)
references
References 66 publications
2
126
0
1
Order By: Relevance
“…Large vesicles filling plant cells are diagnostic of Glomeromycota. Intracellular fungal swellings plus thin-walled hyphae and thickwalled fungal structures in small mucilage-filled intercellular spaces are typical not only of Mucoromycotina in the basal liverwort Treubia [40,41] but also of fungi in the Devonian fossil plant Nothia [42,43]. The ultrastructure of hornwort symbionts is also similar to that of the spores of Endogone flammicorona sporocarps [44].…”
Section: Discussionmentioning
confidence: 94%
“…Large vesicles filling plant cells are diagnostic of Glomeromycota. Intracellular fungal swellings plus thin-walled hyphae and thickwalled fungal structures in small mucilage-filled intercellular spaces are typical not only of Mucoromycotina in the basal liverwort Treubia [40,41] but also of fungi in the Devonian fossil plant Nothia [42,43]. The ultrastructure of hornwort symbionts is also similar to that of the spores of Endogone flammicorona sporocarps [44].…”
Section: Discussionmentioning
confidence: 94%
“…While many liverworts (outlined above) and hornworts [30,31] exhibit interactions with mycorrhizal fungi, mosses generally do not form mycorrhizae [32,33]; for a recent and comprehensive overview see [29]. That mosses do not form mycorrhizae is further corroborated by Wang and colleagues [34], who showed that moss arbuscular mycorrhizal symbiosis genes show high sequence divergence as compared to their homologous counterparts in all other land plants.…”
Section: Fungal Symbioses Exemplify Ancient Plant-microbe Interactionsmentioning
confidence: 94%
“…Sphagnum holds an interesting position amongst mosses, with Cox et al (2004) indicating that Sphagnum and Takakia form a clade sister to all remaining mosses. The paper by Pressel et al (2010) is a comprehensive and fascinating review of fungal symbioses in bryophytes. Fungal symbioses are one of the key attributes of land plants and are widespead in liverworts and hornworts but absent in mosses.…”
Section: Figure 2 Leiosporoceros Dussiimentioning
confidence: 99%